CAUTERIZATION OF GINGIVAL GROWTHS IN THE INTERPROXIMAL POSTERIOR SECTOR THROUGH THE HIPOCRATIC METHOD: COMMUNICATION OF ADVANTAGES AND DISADVANTAGES - Santos-Mercedes, Jhonny J. (2020)
Since ancient times, it has been known that cauterization as a procedure allows the treatment of wounds, but itsconsequences can be harmful in multiple cases. Th e to describe the cauterization of gingival growths in the posterior interproximal sector using the Hippocratic method: advantages and disadvantages. Th e use of cauterization is described, although the electrosurgical unit is mentioned as a simple and effi cient technology in the dental treatment service.